Fixed point and homotopy results for mixed multi-valued mappings in 0-complete partial metric spaces - Adamo, Maria Stella Stella; Vetro, Calogero (Nonlinear Analysis: Modelling and Control, 2015)
We give sufficient conditions for the existence of common fixed points for a pair of mixed multi-valued mappings in the setting of 0-complete partial metric spaces. An example is given to demonstrate the usefulness of our results over the existing results in metric spaces. Finally, we prove a homotopy theorem via fixed point results.
Keywords: fixed points; multi-valued mappings; partial metric spaces